Hospice experiences and approaches to support and assess family caregivers in managing medications for home hospice patients: A providers survey - Joyce, Brian T (2012)
BACKGROUND: Hospice providers need to ensure that informal, unpaid caregivers can safely manage medications to alleviate pain and distressing symptoms in patients near the end of life. AIM: This study characterizes hospice providers' self-reported experiences and approaches to helping caregivers' medication management for home hospice patients. DESIGN: Survey with mixed-method analysis. SETTING/PARTICIPANTS: Surveys were administered to a convenience sample of 98 hospice providers (74 nurses, 6 physicians, 11 social workers, 7 chaplains) from 5 Chicago-based agencies in the United States. RESULTS: Among respondents, 67% rated ensuring proper medication management as “most important” in hospice care delivery, and 33% reported frequently encountering caregivers with problems managing medications. To assess if caregivers had problems managing medications, two categories of approaches emerged from the data: prospective approaches and retrospective warning signs when a problem occurred (e.g. identifying medication nonadherence after observing a sudden patient health decline). Overall, 42% reported using at least one prospective approach, while 38% reported only retrospective signs. To help caregivers manage medications, three categories of approaches emerged: teaching to increase knowledge, supporting existing or simplifying medication management process, and counseling to overcome attitudinal barriers. Overall, 6% reported approaches from all three categories. About 28% frequently experienced difficulty teaching/supporting caregivers with medication management. As much as 47% believed that they would benefit “to a great extent” from additional resources to help caregivers. CONCLUSIONS: Supporting caregivers in medication management is considered important, yet challenging, to hospice providers. Additional resources may be needed to help providers consistently and effectively teach, support, and assess caregivers' medication management.